Privatização da Vale do Rio Doce: valores, manifestações e implicações - Russo, Fátima Ferreira (2002)
This study has investigated how workers have perceived the changes that have occurred at CVRD (Companhia Vale do Rio Doce) with regard to the attitudes of executive officers and to other changes in terms of company values since the organization was privatized. The main aim of this research work has been to verify the values that govern CVRD's administrative proposals after privatization, and how these are reflected in the actions and positioning of the administration at company headquarters. The theoretical referential inc1udes organizational change, theory of values and responsibility of administrative measures in order to understand the current context in which the company finds itself in after the privatization. The fieldwork was conceived under a constructivist paradigm, seeking to uncover perceptions and secondary feelings manifest during interviews and the filling out of questionnaires in order to define past and present values in the organization and the possibilities of a new reality. A complementary phenomenological approach favored the insertion of the author inside the life of this organization, paving the way for dialogs that might apprehend manifestations and implications as to the values people uphold in the transition processo Final deliberations indicate the need for organizational work that would involve workers and directors getting together with the common goal of rediscovering the very meaning ofthe organization. The Vale Viver Program has been brought about as an attempt to proceed in this direction. Values such as 'wear company colors', 'defend company assets' and 'overcome challenges' have always been present in the culture of CVRD. The value 'defend company colors,' which would involve true sharing, is today more the hope for a renewal sometime in the future than an actual living experience in the present. The 'overcome challenges' value is more present in the operations area and the 'defend company assets' value, more c10sely linked to programs such as the Opportunity Bank, reactivated by Vale Viver. This is not to say that Vale Viver is the only way to regain confidence, self-esteem and the co-joining of workers and new administration in the construction of a common base of values, but it is the most visible possibility at a time when a return to the spirit of CVRD would be fundamental for this new stage in its existence.